A risk newborn in the adolescent mother’s perception - Adriana Valongo Zani; Maria de Fátima Garcia Lopes Merino; Élen Ferraz Teston; Deise Serafim; Sueli Mutsumi Tsukuda Ichisato; Sônia Silva Marcon (Rev Rene)
This is a descriptive study with qualitative approach that aimed at understanding the meaning of the concept of risk newborn for adolescent mothers. Data were collected in the period of May 2008 to November 2009, through semi-structured interview, carried out, with 77 adolescent mothers at their own homes. The results show that a considerable number of these mothers ignore the concept and do not consider their infant a “risk baby”. Our research was mainly based on observations and experiences of daily life and very little of it was based on instructions from health professionals. Teenage mothers who received such guidance showed difficulty understanding the concept. The need for these mothers to receive a distinguished service during the prenatal and postpartum period should be considered.